Pengaruh Beban Kerja dan Faktor Lingkungan Fisik Terhadap Tekanan Darah, Denyut Nadi dan Tingkat Kelelahan Pekerja Bagian ARC FURNACE dan ROLLING MILL PT. Inti General Yaja Steel Semarang - Nurullita, Ulfa; Suhartono, Suhartono; Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT Background: The existence of work efficiency can be reached with balancing work capacity and increase capacity in the working environment. One factor in the working environment that cause work inefficiency is physical factor namely heat stress, noise and lighting. The influence of physical factors are indicated by physical performance of the worker’s blood pressure and fatigue level. Objective: to find out the influence of work capacity and physical factors in the working environment on the blood pressure, pulse, fatigue level of worker in Arc Furnacearea and Rolling Mill section, PT Inti General Yaja Steel Semarang. Methode: Type of the research was quasy experimental with one group pre and post test design. The population were 178 worker and 47 workers were taken in this research. Confounding factors was cigarettes, cafein, drug consumption, and nutrition status. Result: There was found differences of blood pressure before working and after working (systole; p- Wilcoxon Sign Ranks = 0,001, diatole; p- Wilcoxon Sign Ranks, = 0,003). The average before working (systole=119,7 mmHg, diastole= 84 mmHg) was higher than after working (systole=107,2 mmHg, diastole= 78,9 mmHg). There was also differences of pulse rate before working and after working (p-paired t test= 0,001). The average of pulse before working (81,5 times/minute) was lower than after working (87,5 times/minute). There was found differences of fatigue level before working and after working (p- Wilcoxon Sign Ranks=0,001). The average of fatigue level before working was measured 253,2 millisecond lower than after working (290,7 milisecond). Conclusion: There is found differences of blood pressure, pulse and fatigue level before working and after working. There are no differences of blood pressure transition, pulse transition and fatigue transition based on heat stress, noise, lighting, work capacity, cigarettes, cafein, drug consumption and nutrition status. Keywords : work capacity, physical factor , working environment, blood pressure, fatigue level